Analisis Gramatika pada Abstrak Prosiding (The 1 International Conference On Business and Accounting Studies, University of Jember) - Endang Kurniati (Fakultas Ekonomi dan Bisnis Islam, 2017)
This research is done to investigate the grammar error on the abstracts of proceeding. The finding portrayed some grammatical errors in proceedings written out in English. Grammar takes important role in writing good proceedings so that the readers are able to achieve the benefits of it. Errors in grammar automatically cause misunderstanding and misinterpretation. Through descriptive qualitative method employed in this research it revealed that the writer’s prior knowledge on grammatical rules in Indonesian language had caused problems. Five abstracts were taken as the main source of the data. The abstracts were taken from proceedings published by University of Jember. From the findings it can be concluded that the writers have big deals in giving article, giving ending -s/-es in present form, determining correct preposition, choosing appropriate words, forming passive, adding suffix, and giving final ‘s in possessive and determining plural and singular. All those problems were suspected as the impact of writers’ prior knowledge on the source language. The writers were still in adaptation on using grammatical rules in the target language, English in this case. The formulation of some phrases and sentences were often come in source language rules. Finally, the result of this research is expected to be able to give meaningful contribution to the reader and the following researcher in the same field.